Butyrate production from high-fiber diet protects against lymphoma tumor. Issue 10 (2nd October 2016) - Wei, Wei; Sun, Wei; Yu, Shanshan; Yang, Yu; Ai, Limei
Abstract: Gut microbiota and dietary fiber are critical for protecting body from obesity, diabetes and cancer. Butyrate, produced in the gut by bacterial fermentation of dietary fibers, is demonstrated to be protective against the development of colorectal cancer as a histone deacetylase (HDAC) inhibitor. We report that high-fiber diet and butyrate significantly inhibited the growth lymphoma tumors. Butyrate induced apoptosis of lymphoma tumor cells and significantly up-regulated histone 3 acetylation (H3ac) level and target genes such as Fas, P21, P27. Our results unravel an instrumental role of fiber diet and their metabolites on lymphoma tumor and demonstrate an intervention potential on the prevention and therapy of lymphoma.